2014
DOI: 10.1007/s40291-013-0082-z
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of the P450 Oxidoreductase *28 Single Nucleotide Polymorphism with the Lipid-Lowering Effect of Statins in Hypercholesterolemic Patients

Abstract: The POR*28 allele was not associated with the lipid-lowering effect of atorvastatin and the results were replicated in an independent simvastatin-treated population. The hypothesized effect of the POR*28 allele on the lipid-lowering response to CYP3A-metabolized statins can potentially be masked by relevant confounding or uncontrolled factors; therefore, further studies in different populations are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…POR transfers electrons from NADPH to CYP3A enzymes to enable their catalytic activity [21,22]. The human POR gene is highly polymorphic.…”
Section: Introductionmentioning
confidence: 99%
“…POR transfers electrons from NADPH to CYP3A enzymes to enable their catalytic activity [21,22]. The human POR gene is highly polymorphic.…”
Section: Introductionmentioning
confidence: 99%
“…With the total length of 72 kb, the POR gene is highly polymorphic . The genetic polymorphisms of POR could affect the efficacy of the drugs such as tirapazamine, mitomycin C, cyclophosphamide, midazolam, warfarin, tacrolimus, atorvastatin, clobazam and nifedipine directly or mediated by CYP enzymes . In addition, our study has found that POR rs2868177 could significantly increase CYP2B6 activity as measured by bupropion hydroxylation (data not published).…”
Section: Discussionmentioning
confidence: 80%
“…Children with familial hypercholesterolemia (FH) carriers of POR*28 allele seem to be associated with reduced effect of atorvastatin on total cholesterol and LDL-C, so this allele identifies subjects that may require higher atorvastatin doses to achieve full therapeutic benefits [5]. Nevertheless, published data are discordant and considering the current stateof-the-art further studies involving wider and different populations are required [6].…”
Section: What Is New About Statins?mentioning
confidence: 99%